INDONESIA SOEs BUILDING COMPETITIVE ADVANTAGE - Lenggogeni, Lenggogeni; Nandan Limakrisna (Dinasti Publisher, 2020)
This article argues that the State-Owned Enterprises (SOEs) are still incapable of Achieving the expected marketing performance. The low performance is due to the incapabilities of the SOEs in competition with other companies, inaccuracies in innovation both in terms of products, processes, and market innovation, as well as lack of coordination in the creation of multifunctional product value. The article is based on an empirical survey involving 141 state-owned companies. The results of analyzes indicate that SOEs have created innovative, cross-functional coordination, and value creation, but still weak in making product innovation and market value creation. Innovation has proven links with cross-functional coordination, while the innovation and cross-functional coordination effect on product value creation. However, Innovation has a predominant influence on value creation in comparison with cross-functional coordination. Meanwhile, the innovation by the SOEs has not been able to create a competitive advantage, while cross-functional coordination has a dominant influence on competitive excellence, Compared to the effect of innovation and value creation.